2016
DOI: 10.3390/rel7050052
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Field Education in and with Congregations and Religiously-Affiliated Organizations in a Christian Context

Abstract: Recent attention to human spirituality, research on congregationally-related practice, and growth in employment within religiously-based organizations energize the creation of educational initiatives to prepare future professionals for competent social work practice within these settings. Internship experiences with congregations and religiously-affiliated organizations (RAOs) play a pivotal role in delivering the competencies required by the social work accreditation body. Conceptual tools are needed for unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Social work literature examining field education and spirituality remains limited, and explicitly considers only a few key areas: field education with religiously affiliated agencies, challenges to students' worldviews in field education, and models for integrating spirituality into field supervision and education (see for example: Colvin & Bullock, 2017;Harris et al, 2016;Okundaye et al, 1999). A brief review of the literature revealed that many of these explorations consider Christian student experiences, Christian social service agencies, and perspectives of Christian-affiliated social work schools.…”
Section: Social Work Field Education and Spiritualitymentioning
confidence: 99%
“…Social work literature examining field education and spirituality remains limited, and explicitly considers only a few key areas: field education with religiously affiliated agencies, challenges to students' worldviews in field education, and models for integrating spirituality into field supervision and education (see for example: Colvin & Bullock, 2017;Harris et al, 2016;Okundaye et al, 1999). A brief review of the literature revealed that many of these explorations consider Christian student experiences, Christian social service agencies, and perspectives of Christian-affiliated social work schools.…”
Section: Social Work Field Education and Spiritualitymentioning
confidence: 99%
“…Social work literature examining field education and spirituality remains limited, and explicitly considers only a few key areas: field education with religiously affiliated agencies, challenges to students' worldviews in field education, and models for integrating spirituality into field supervision and education (see for example: Colvin & Bullock, 2017;Harris et al, 2016;Okundaye et al, 1999). A brief review of the literature revealed that many of these explorations consider Christian student experiences, Christian social service agencies, and perspectives of Christian-affiliated social work schools.…”
Section: Social Work Field Education and Spiritualitymentioning
confidence: 99%
“…As a result, social workers engaging with political settings may face limited assistance in managing interprofessional relationships and the political dilemmas common to this practice. Ethical challenges are not unique to social workers in interprofessional political contexts, as ethical challenges have been identified for social workers in other interprofessional settings, including legal aid (Schoeneman 2017), religious congregations and religiously affiliated organizations (Harris et al 2016), law enforcement (Dickinson 2017), and the criminal and juvenile justice systems (Albert 2018). Social workers in interprofessional settings may have limited educational exposure to these challenges and few models to turn to for advice.…”
Section: Literature Reviewmentioning
confidence: 99%